Users’ preferences towards social attributes of creative placemaking - Ramli, Nurul Atikah (2020)
Rapid urban development with the increasing population growth often led to social isolation and a diminishing cultural identity. Through this challenge, the government has embraced placemaking as a strategy to sustain inclusive cities and communities. Malaysia has also made efforts in creating more inclusive urban environment to secure cultural identity by branding the Kuala Lumpur as a Cultural and Creative City. Creative placemaking is an emerging field of practice that purposefully leverages the power of the arts, culture, and creativity to serve the needs of the urban community. However, there is a lack in the creative practice in terms of the forms and types of activities that should be offered to support users’ social needs and preferences. To date, a multidimensional evaluation of creative placemaking which subjectively considers the social aspect and urban design has not been adequately explored. The aim of the study is to incorporate urban design social attributes as a framework to establish a successful creative placemaking within the Kuala Lumpur city center. This study examines the preferences of users regarding the social attributes of place and the factors influencing them. RIUH, one of the social initiatives practicing creative placemaking in places within Kuala Lumpur was selected as a case study. This study was initiated with a quantitative methodology, based on self-completion questionnaires by 340 respondents. It is followed by qualitative methodology by conducting field observation using photographic recording technique to document the actual scene of the study area and strengthen the questionnaire survey findings. The quantitative data were analyzed using SPSS version 21 whereas qualitative data using content analysis. The results of users’ preference, field observation, and answers from open-ended questions were then synthesized. Findings revealed social attributes of place in creative placemaking such as inclusiveness, value, diversity, and vitality of place are notable. These sets of social attributes of the place were determined by demographic profile, their pattern of engagement, and place experience. The findings contribute to a better understanding of social attributes of place to be provided in creative placemaking and emphasize the significance of such environments in promoting social opportunity.